Delayed-Onset Muscle Soreness of the Psoas Major Muscle Following Abdominal Training: Case Report - Laura Gabriela Silva; Victor Sudário Takahashi; José Luiz Masson de Almeida Prado; Henrique Shimidu; Luís Henrique Paiva D’Elia; Márcio Luís Duarte (Acta Medica)
Edema of the psoas major muscle can indicate various pathologies, such as infection, malignancy, and trauma, but it can also result from benign causes like delayed-onset muscle soreness (DOMS). This article presents the case of a 44-year-old female patient who developed DOMS in the psoas major after participating in an intense abdominal workout. The patient reported hip pain that began a day after the workout, which was confirmed by magnetic resonance imaging (MRI) revealing significant edema in the psoas major muscles, particularly on the right side. Conservative treatment with rest and analgesics led to full recovery within two weeks. DOMS, typically associated with eccentric exercises, can be mistaken for more serious conditions, but its recognition is crucial to avoid unnecessary investigations and interventions. This case highlights the importance of clinical history and imaging findings in distinguishing DOMS from other causes of muscle edema, emphasizing the need for accurate diagnosis to ensure appropriate management.